Thymidylate synthase drives the phenotypes of epithelial-to-mesenchymal transition in non-small cell lung cancer - Siddiqui, Mohammad Aarif; Gollavilli, Paradesi Naidu; Ramesh, Vignesh; Parma, Beatrice; Schwab, Annemarie; Vazakidou, Maria Eleni; Natesan, Ramakrishnan; Saatci, Ozge; Rapa, Ida; Bironzo, Paolo; Schuhwerk, Harald; Asangani, Irfan Ahmed; et al. (British Journal of Cancer, 2020)
Background: Epithelial-to-mesenchymal transition (EMT) enhances motility, stemness, chemoresistance and metastasis. Little is known about how various pathways coordinate to elicit EMT’s different functional aspects in non-small cell lung cancer (NSCLC). Thymidylate synthase (TS) has been previously correlated with EMT transcription factor ZEB1 in NSCLC and imparts resistance against anti-folate chemotherapy. In this study, we establish a functional correlation between TS, EMT, chemotherapy and metastasis and propose a network for TS mediated EMT. Methods: Published datasets were analysed to evaluate the significance of TS in NSCLC fitness and prognosis. Promoter reporter assay was used to sort NSCLC cell lines in TSHIGH and TSLOW. Metastasis was assayed in a syngeneic mouse model. Results: TS levels were prognostic and predicted chemotherapy response. Cell lines with higher TS promoter activity were more mesenchymal-like. RNA-seq identified EMT as one of the most differentially regulated pathways in connection to TS expression. EMT transcription factors HOXC6 and HMGA2 were identified as upstream regulator of TS, and AXL, SPARC and FOSL1 as downstream effectors. TS knock-down reduced the metastatic colonisation in vivo. Conclusion: These results establish TS as a theranostic NSCLC marker integrating survival, chemo-resistance and EMT, and identifies a regulatory network that could be targeted in EMT-driven NSCLC. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2020-10-16